HUBUNGAN PENGETAHUAN ERGONOMI DAN SIKAP KERJA PADA PERAWATAN LUKA DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PERAWAT DI RSU dr. H. KOESNADI BONDOWOSO - Ishana Balaputra; Adi Heru Sutomo (Berita Kedokteran Masyarakat (BKM), 2017)
Ergonomics knowledge and work posture of nurses on wound care with musculoskeletal disorder in dr. H. Koesnadi BondowosoPurposeThe purpose of this paper was to determine the association between knowledge of ergonomics and work attitude on wound care with complaints of musculoskeletal disorders in hospital nurses. MethodsA cross-sectional study was conducted involving questionnaires distributed to 29 nurses working in the surgical and internal departments who met the inclusion and exclusion criteria. ResultsThere was no significant correlation between sex, age, and education level with musculoskeletal disorder (p> 0.05). Knowledge of ergonomics, work attitude, and length of service were associated with musculoskeletal disorder. ConclusionsEducation and training on proper ergonomics and work posture should be introduced in the workplace to reduce the risk of musculoskeletal disorder among the nurses working in different settings